Efektivitas Model Pembelajaran TPS Berbantuan Permainan Tradisional dan NHT Berbantuan Permainan Tradisional terhadap Prestasi Belajar Siswa pada Materi Aritmatika Sosial - Muzayanah Muzayanah; Sudargo Sudargo; Sutrisno Sutrisno (Jurnal Kualita Pendidikan, 2021)
This study aims to determine the effectiveness of learning model TPS and NHT assisted traditional game to student achievement on the social arithmetic material. This study is quantitative research. The population in this study student of class VII SMP N 3 Larangan Brebes of the 2017/2018 school year. Sampling using cluster random sampling technique. The data collection technique is the method of observation, documentation, and tests. Data analysis techniques with one way analysis of variance, simple linear regression, and proportion test a with a significant level of 5%. The results showed that: (1) there were differences in the ability to student achievement with TPS learning model assisted by traditional game and NHT learning model assisted by traditional game, and conventional with the results of ANOVA, (2) there is an effect of student activity learning on the student achievement who get the TPS and NHT models assisted by the traditional game with simple linear regression, and (3) student achievement with the TPS and NHT models assisted traditional game reach the minimum completeness criteria.